Perspective of postpartum depression theories: a narrative literature review - Abdollahi, Fatemeh; Lye, Munn Sann; Zarghami, Mehran (Medknow Publications and Media Pvt., 2016)
Postpartum depression is the most prevalent emotional problem during a women's lifespan. Untreated postpartum depression may lead to several consequences such as child, infant, fetal, and maternal effects. The main purpose of this article is to briefly describe different theoretical perspectives of postpartum depression. A literature search was conducted in Psych Info, PubMed, and Science Direct between 1950 and 2015. Additional articles and book chapters were referenced from these sources. Different theories were suggested for developing postpartum depression. Three theories, namely, biological, psychosocial, and evolutionary were discussed. One theory or combinations of psychosocial, biological, and evolutionary theories were considered for postpartum depression. The most important factor that makes clinicians' choice of intervention is their theoretical perspectives. Healthcare providers and physicians should help women to make informed choices regarding their treatment based on related theories.